Posisi Republik Islam Iran Dalam Program Nuklir Dalam Perspektif Amerika Serikat - Hendra Maujana Saragih; Mega Murti Lestari; Nurmaida Muis (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
The focus of the research is about foreign policy of United States of America which related with Iran’s Nuclear program under Donald Trump administration.Donald Trump refuse Iran nuclear program because Iran can make nuclear weapons and becoming a threat to world peace especially for Middle East Region. This research is qualitative andthe research method is descriptiveaimed to describe United States of America’s foreign policy under Donald Trump administration which different with the former United States of America’s President. Data collection method used is library, such as books, journals, and articles. Theoretical frameworks used by this thesis to analyze the problem are foreign policy analysis and national interest analysis.The result of this research indicate that Donald Trump give maximum pressure so that Iran can accept the new more comprehensive dealbyexit from Iran’s Nuclear agreement 2015 also known as Joint Comprehensive Plan of Action (JCPOA)and would reimpose sanctions that had been suspended pursuant to the agreement and give additional sanctions to Iran.